GIS implementation : on utilizing previous customer information for marketing enhancement / Muhammad Safwan Ahmad - Ahmad, Muhammad Safwan (2018)
Management of previous customer information recently becomes very crucial in any business. Most of the business owner especially retailer do not know how to make use of it. This paper is focused on one of the Hino dealer in Malaysia which is Edaran Riz Sdn Bhd. The main problem is about the previous customer information is not fully utilized. From interview with Edaran Riz Sdn Bhd, they used the data of their customer just only for record, but they know it is a very precious thing that cannot be leaked out to their competitors. But, they have limitation in extracting extra information from the customer database and difficult for them to enlarge their marketing strategy from the record of the customer. This project aims to enhancing the sales performances of commercial vehicle retailer with the aid of GIS. In fulfilling the aim, it need to be done by GIS implementation in enhancing the database of previous customer, evaluate the criteria that contribute to the previous sales of commercial vehicle and determine a new potential area of future customer from sales performances. GIS could help in dealing with several factors simultaneously which need to be considered while planning marketing strategies. GIS is a system of computer hardware and software, designed to allow users to collect, manage, analyses and retrieve large volume of spatially referenced data and associated attribute data collected from a variety sources. In marketing, the GIS is used for selecting alternative place for potential location of future and existing customer and also for optimal choosing the best place to make a marketing move. This research is about to enhance the marketing strategies into the next level which by the help of GIS